Azimuthal harmonics in small and large collision systems at RHIC top energies - STAR Collaboration (Physical Review Letters, 2019)
The first (vfluc1), second (v2), and third (v3) harmonic coefficients of the azimuthal particle distribution at midrapidity are extracted for charged hadrons and studied as a function of transverse momentum (pT) and mean charged particle multiplicity density ⟨Nch⟩ in U+U (√sNN=193 GeV), Au+Au, Cu+Au, Cu+Cu, d+Au, and p+Au collisions at √sNN=200 GeV with the STAR detector. For the same ⟨Nch⟩, the vfluc1 and v3 coefficients are observed to be independent of the collision system, while v2 exhibits such a scaling only when normalized by the initial-state eccentricity (ϵ2). The data also show that ln(v2/ϵ2) scales linearly with ⟨Nch⟩−1/3. These measurements provide insight into initial-geometry fluctuations and the role of viscous hydrodynamic attenuation on vn from small to large collision systems.
32 citations (Crossref) [2023-10-31] Finch
Keywords: Azimuthal harmonics; Charged hadrons; Charged particle multiplicities; Charged particles; Colliding beam accelerators; Collision systems; Germanium compounds; Gold compounds; Harmonic coefficients; Initial state; Particle distributions; Transverse momenta; dept.phy; peer-reviewed